Improving numeracy in Trinidad and Tobago: Report on a primary-level teacher education strategy - Byron, Maria K.
A university training programme was developed as part of a project to improve the standard of primary-level numeracy in Trinidad and Tobago. Fifty-eight primary level teachers completed training to conduct workshops and provide field supervision in developmental and remedial mathematics. The programme of work, including activities and assessment techniques, is presented. The evaluation of both the university programme and the workshop training provides a background for reviewing the project's status
Special Issue: Primary education in the Commonwealth Caribbean, ed. by Donald G. Wilson
Keywords: Primary school teachers